41 Content Analysis of the Recommendations from Project Echo Ontario Autism. (21st October 2022) - Jane, Alanna; Kanisberg, Lisa; Patel, Anmol; Eldon, Salina; Anagnostou, Evdokia; Brian, Jessica; Penner, Melanie
Abstract: Background: The rising prevalence of autism spectrum disorder (ASD) diagnoses has caused an increased number of community practitioners to care for this population. However, community practitioners report a lack of knowledge and confidence in treating these patients, resulting in unmet healthcare needs. The Extension of Community Healthcare Outcomes (ECHO) Autism model aims to address this through case-based and didactic learning to help guide community practitioners in providing comprehensive, best-practice care for ASD screening, diagnosis, and management of co-occurring conditions. Each ECHO session involves a case presentation followed by a list of recommendations generated by community participants and an interdisciplinary 'hub' team. While ECHO Autism has been shown to improve physicians' abilities to care for children with ASD in their practices, recommendations stemming from ECHO cases have yet to be characterized and may help guide future care. Objectives: To quantify and characterize the common categories within ECHO Autism Ontario case recommendations. Design/Methods: A content analysis of 422 recommendations from 61 ECHO cases was conducted to identify categories of recommendations and their frequencies. Three researchers independently coded recommendations from five ECHO cases, from which an original coding guide was developed. The researchers then independently coded the remaining cases and met regularly with the ECHO lead to modify and consolidate the codes and coding guide. From there, categories and sub-categories from the various codes were identified. Finally, the frequencies of each code and category were calculated. Results: Fifty-seven codes were included in the final coding guide and grouped into eight broad categories. Categories included: 1) diagnosis; 2) concurrent mental and physical health conditions; 3) referrals to allied health providers and other specialists; 4) accessing community resources, such as parent and sibling support groups; 5) providing education and guidance to physicians, patients, and families; 6) management strategies such as nutrition, physical activity, and social skills; and 7) patient and family-centered care. A COVID-19 category was added, as many of the later recommendations were adapted to online service delivery. An analysis of the frequency of codes found that 1, 384 total in-text codes were distributed amongst the various categories. The three highest frequencies of categories were providing general guidance and education (22%), accessing resources (16%), and referrals (15%). Conclusion: This is the first time recommendations from ECHO Autism have been characterized and quantified. Our results, particularly the most common category of providing general guidance and education about ASD, show there is still important work to be done with educating clinicians and families about aspects of ASD. Furthermore, findings from this study should inform Pediatrics residency programs about real-world knowledge gaps in ASD care, and may help create more tailored ASD training programs and educational materials.